Meningkatkan Literasi Siswa Tentang Mitigasi Gas Rumah Kaca Melalui Proyek Pembuatan Biochar Dari Limbah Organik Sekolah di SMP Negeri 7 Muaro Jambi - Istiqomah, Istiqomah; Damris, Muhammad; Hasibuan, Muhammad Haris Effendi (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to improve students' literacy on greenhouse gas mitigation through a biochar-making project from school organic waste. This study uses a qualitative descriptive approach with a project-based learning model. The study was conducted at SMP Negeri 7 Muaro Jambi with 30 class VII G students as subjects. Data were obtained through observation, interviews, questionnaires, and documentation. The project was carried out by actively involving students in the biochar-making process, starting from waste collection, the pyrolysis process, to analyzing the benefits of biochar. The results showed that student involvement in the project significantly increased their understanding of greenhouse gases, their impacts, and mitigation solutions through biochar. Students were able to explain the concept of GHG, mention its negative impacts, understand the biochar-making process, and demonstrate an attitude of caring for the environment. In addition, teachers responded positively to the project and planned to integrate it into P5RA activities. Thus, the biochar production project has proven to be an effective method in improving students' literacy on GHG mitigation and can be used as an alternative for contextual learning based on the environment in schools.